2018
DOI: 10.1177/0142331218765614
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical parameter identification of two-mass drive system based on variable forgetting factor recursive least squares method

Abstract: Alternating current (AC) motor drive systems are widely used and their performances are greatly affected by motor parameters and load disturbances, so it is necessary to identify and observe their moment of inertia, the viscous friction coefficient and load torque. This paper presents an identification method combined a Luenberger observer and the variable forgetting factor recursive least squares method (FFRLSM), which does not require the torque sensor but a position encoder and can identify the moment of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Figure 4 shows a simplified block diagram of the speed control system [41]. Apparently, deriving the elastic torque from electrical parameters will not allow us to find the peak dynamic loads at the eigenfrequencies of the mechanical system (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Besides, this method does not provide sufficient accuracy in case of variable frequency drives.…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows a simplified block diagram of the speed control system [41]. Apparently, deriving the elastic torque from electrical parameters will not allow us to find the peak dynamic loads at the eigenfrequencies of the mechanical system (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Besides, this method does not provide sufficient accuracy in case of variable frequency drives.…”
Section: Problem Formulationmentioning
confidence: 99%
“…In Russia, it is mainly researched by the Ivanovo State Energy University [7][8][9][10]. The problem is also covered in [11][12][13][14][15]. Dynamic stability improvement and reducing the influence of interference are the problems covered in [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…All the more so as the identification of the moment of inertia, the viscous friction coefficient and the load torque and setting their values is very challenging. The DT is an alternative method for representing the two-mass drive system [25].…”
Section: B Digital Twin Description and Implementationmentioning
confidence: 99%
“…The systems are assumed to be two-mass drive systems with a flexible shaft connecting the motor and the (elastic) load. This topic has received great attention from the scientific community, because the identification of mechanical parameters of the two-mass drive systems is not straightforward [25]. To the best of the authors' knowledge, the key point is the design and implementation of the DT for the whole system, including the virtual representation of all mechanical and electrical components including the load, the main nonlinearities (backlash and friction), and the corresponding control system.…”
Section: Introductionmentioning
confidence: 99%
“…Damping ratios and natural frequencies of linear-time-invariant flexible mechanical systems are estimated with least-squares error optimization (Chee et al, 2010). Authors identified moment of inertia, viscous friction coefficient, and load torque of two-mass drive system by combining a Luenberger observer and the variable forgetting factor recursive least-squares method (Ke et al, 2018). Flexible structures such as beams (Abreu et al, 2012; Bu et al, 2003; Saad et al, 2013; Afshari et al, 2014) and cantilever plate (Dong et al, 2006) are studied with Auto-Regressive eXogenous (ARX), Auto-Regressive Moving Average eXogenous (ARMAX), Finite Impulse Response (FIR), and Eigensystem Realization Algorithm (ERA) models to estimate dynamic models.…”
Section: Introductionmentioning
confidence: 99%